(3ePGcQI GdCMQGQ aj GdebGe hGdCSaGQs - (3CMeO Hf Hjdjc GdeMSfj GdXGgQj GdTGaYj GdeUQj, TgGH GdOjf,J (B753 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj LeYJ aj gPg GdChQGb fHPI jSjQI ef dWaGA GdHdZGA, hfXe GdTYQ, heMGSf GdMceGA s
(3BNQgG (B:s
(3bGd LGeYg hdjcf gPG BNQ GdeLehY, hGddg GSCd Cf jfaY Hg bGQFg heSJeYg Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdYfhGfGJ HNW GdKdKs
(3jdjg cJGH BNQ aj ZjQ GdCOH aj fMh (B60 (3hQbIs
(3ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs